A functional Au array SERS chip for the fast inspection of pesticides in conjunction with surface extraction and coordination transferring. Issue 18 (12th August 2019) - Ouyang, Lei; Dai, Pei; Yao, Ling; Zhou, Qian; Tang, Heqing; Zhu, Lihua
Abstract : An organic solvent-compatible Au array SERS chip was developed for pesticide detection in conjunction with surface extraction and coordination transferring. Abstract : The fast inspection of the pesticide residues on fruits and vegetables requires the development of facile, sensitive and accurate methods. Surface enhanced Raman scattering (SERS) is a promising way to provide a fast inspection method, which requires significant improvements in the reproducibility and feasibility. In the present work, an SERS method was developed for the fast inspection of pesticides on fruit peels in conjunction with surface extraction and coordination transferring. In this new method, the residual pesticides were directly extracted from fruit peels with an appropriate extraction solution and then quantitatively transferred onto an organic solvent-compatible Au array SERS chip through the strong chemical interactions between the heteroatoms in the pesticides and the gold surface. The functional SERS chip was fabricated by the interfacial assembly of an Au array on a membrane, which produced dense and uniformly distributed SERS hot spots and enabled compatibility with random curvature surfaces and handheld Raman spectrometers. As a proof of concept, sulfur atoms containing thiram on apples were detected at a concentration as low as 5 ng cm −2 with good reproducibility (relative standard deviation lower than 10%). The strong interactions between the sulfur atoms and gold surface during the coordination transferring process were confirmed by the enhanced vibrations of the specified bands occurring in both the Raman and IR spectra. This surface extraction-coordination transferring-based method holds wide applicability for heteroatom-containing pesticides, as demonstrated by the detection of various S- and P-containing pesticides.